The University in the 1990s: Crisis or Predicament? - Sibley, W. M. (Canadian Journal of Higher Education, 1993)
The financial difficulties which our universities are currently encountering are not without precedent, as a brief retrospective look at conditions in the 1930s will attest. However, the "decision space " in which we must operate today is far more circumscribed than at any time in the past. External constraints continue to increase in number and severity; the contemporary academic culture has greatly weakened old institutional values and identities; and governance structures have become inordinately complex, cumbersome, and ill-adapted to deal with existing realities. In these circumstances, strident demands for "greater accountability " and "stronger leadership " cannot really be met. It is imperative that we not only address certain pressing problems but also identify several genuine system contradictions, which cannot be evaded and sooner or later must be resolved. Any credible agenda for renewal must be based on new paradigms of participation and models of governance, that will enable us to create patterns of decision-making far more suited to cope with emerging realities than the outmoded forms embedded in our current systems.